Pirates of the Caribbean : dead men tell no tales - Roenning, Joachim, 1972-; Sandberg, Espen; Depp, Johnny; Bardem, Javier, 1969-; Rush, Geoffrey, 1951-; Zanelli, Geoff, 1974- (Burbank, CA : Walt Disney Studios Home Entertainment, 2017)
Captain Jack Sparrow searches for the Trident of Poseidon.
Originally released as a motion picture in 2017.
Sequel to the film "Pirates of the Caribbean, on stranger tides" (2011).
Dolby digital 5.1, wide screen 2.40:1.
Features: First mate confidential.
Camera, Paul Cameron ; production designer, Nigel Phelps ; editors, Roger Barton, Leigh Folsom Boyd ; music, Geoff Zanelli.
Johnny Depp, Javier Bardem, Geoffrey Rush, Brenton Thwaites, Kaya Scodelario.
Keywords: Pirates -- Drama; Supernatural -- Drama; Action and adventure films; Fiction films; Video recordings for the hearing impaired; Feature films; Fantasy films